2011
DOI: 10.1113/jphysiol.2011.216309
|View full text |Cite
|
Sign up to set email alerts
|

Purinergic signalling mobilizes mitochondrial Ca2+ in mouse Sertoli cells

Abstract: Non-technical summary In mammalian testes, Sertoli cells play a key physiological role in germ cell development. Previous research has implicated local ATP release as a potential mechanism of Sertoli cell stimulation. We show that, in mouse Sertoli cells, two different receptor proteins are activated by ATP. Receptor activation, in turn, causes elevation of calcium ion levels inside the cells. By using a novel method to visualize such calcium signals, we identify mitochondria as essential elements of calcium r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
34
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 60 publications
4
34
0
Order By: Relevance
“…mRNA for P2Y 1 , P2Y 2 and P2X4 and P2X7 receptors was expressed in cultured rat Sertoli cells [214]. It has been claimed that mitochondria are essential components of Sertoli cell signalling that control purinergic Ca 2+ responses, mediated by P2X2 and P2Y 2 receptors [414].…”
Section: Testismentioning
confidence: 99%
“…mRNA for P2Y 1 , P2Y 2 and P2X4 and P2X7 receptors was expressed in cultured rat Sertoli cells [214]. It has been claimed that mitochondria are essential components of Sertoli cell signalling that control purinergic Ca 2+ responses, mediated by P2X2 and P2Y 2 receptors [414].…”
Section: Testismentioning
confidence: 99%
“…In 1992, a very influential study (3) showed that mitochondrial Ca 2+ uptake was a genuine cellular mechanism. Recently, investigations in diverse tissues, including cardiac and skeletal muscle, liver cells, and neurons, have raised the possibility that mitochondria also serve as large and dynamic physiological buffers for Ca 2+ (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15). However, this point has been debated (16), and forces the question: How much Ca 2+ moves into and out of the mitochondria under normal conditions?…”
mentioning
confidence: 99%
“…The P2X2R, P2X3R, and P2X5R subtypes have been identified in various germ cell types, whereas Sertoli cells express P2X2R, P2X3R, and P2X7R (Glass et al, 2001a) as well as the calcium-mobilizing P2Y 2 R (Rudge et al, 1995). Calcium signals generated by activated P2XRs and P2YRs in mouse Sertoli cells are coupled to mobilization of mitochondrial calcium (Veitinger et al, 2011). In addition to P2XRs and P2YRs, A 1 Rs have been found in the crude particulate preparation from rat testis and Sertoli cell enriched cultures (Conti et al, 1988; Monaco et al, 1986; Stiles et al, 1986).…”
Section: Purinergic Regulation Of the Hypothalamic-pituitary-gonadmentioning
confidence: 99%